Cortical reorganisation and tinnitus following restricted peripheral deafferentation in the ferret: targeting neural plasticity by optogenetic silencing - Gold, J (2015)
Subjective tinnitus is the perception of a sound in the absence of an environmental source, and is thought to derive from maladaptive neuroplasticity that occurs following hearing impairment. However, the underlying structural and functional mechanisms remain unresolved. Our aims were thus to develop a model of trauma-induced tinnitus, and to investigate whether primary auditory cortex played a causal role. We tested ferrets on a gap-in-noise detection task to assess auditory temporal processing, which is impaired in tinnitus and hearing loss. Ferrets displayed robust gap-detection performance, with sensitivity that varied with the frequency content and bandwidth of the acoustic carrier noise, as we also found in human subjects tested on a comparable task. This confirmed the ferret as a relevant model of auditory temporal processing. To investigate hearing-loss-related neuroplasticity, ferrets underwent a partial, unilateral lesion of the spiral ganglion (SG), replicating aspects of otopathology described in tinnitus. Behaviourally, this lesion induced heterogeneous outcomes, with some ferrets displaying temporal processing impairments, and others showing post-lesion adaptation. These behavioural outcomes correlated with features of the auditory brainstem response, indicating a possible predisposition towards adaptation/maladaptation. Anatomical and physiological analysis of auditory cortical cells showed evidence for lesion-related central neuroplasticity that correlated with each animal’s behavioural phenotype. We finally sought to determine whether these cortical changes underpinned the behavioural changes described. The optogenetic protein Archaerhodopsin-T was expressed bilaterally in auditory cortical neurons of SG-lesioned ferrets, allowing suppression of neural spiking during behaviour. Only contralesional suppression mediated any substantive behavioural effects, improving the performance of animals with temporal processing impairments, and impairing performance in animals with post-lesion improvements. The mechanistic basis for these effects was shown, through physiological recordings, to derive from optogenetic enhancements in cortical temporal processing. Together, these results suggest that primary auditory cortex plays an important role in mediating deafferentation-related neuroplasticity, suggesting possible strategies for remediation of the maladaptive processing potentially underpinning tinnitus in humans.